Long term effects of surgically assisted rapid maxillary expansion without performing osteotomy of the pterygoid plates - Seeberger, Robin; Kater, Wolfgang; Davids, Rolf; Thiele, Oliver C. (Journal of cranio-maxillofacial surgery, 2010)
Surgically assisted rapid maxillary expansions (SARME) are commonly used to widen the maxilla. This study evaluates long term stability of surgically assisted rapid palatal expansion without performing osteotomy of the pterygoid plates and its effects on nasal airway volume.
Online veröffentlicht am 5. August 2009
Gesehen am 12.07.2023